Improving the yield of Jatropha curcas's FAME through sol–gel derived meso-porous hydrotalcites. (February 2016) - Helwani, Z.; Aziz, N.; Kim, J.; Othman, M.R.
Abstract: The conversion of fatty acid methyl ester (FAME) from triglycerides using heterogeneous catalysis has gained increasing interest due to the prospect of increased yield at reduced operating costs and reaction conditions. In this paper, meso-porous hydrotalcite was used to catalyze jatropha oil into FAME with relatively higher yield at atmospheric pressure and relatively low reaction temperature. The molar ratio of methanol to oil required was relatively low and the conversion was completed within few hours of reaction time. The reaction was promoted when moderate calcination temperature was applied, the disordered structure of the catalyst was maintained, counterbalance anions was removed, and phase transitions within the oxide lattice was induced. Despite the observed deactivation during successive reaction cycles due to adsorption of residual triglycerides, the catalyst performance was restored effectively by air-re-calcination. Highlights: Effective meso-porous synthetic anionic clay catalyst. Significant conversion of methyl-ester from Jatropha curcas oil was achieved. The catalyst was highly regenerable. The catalyst was not prone to leaching.